Perancangan Alat bantu Tanam Bibit Padi Sawah Secara Ergonomis dalam Upaya Meningkatkan Efisiensi Waktu Tanam : Studi Kasus Kecamatan Lakbok Jawa Barat - Sarwoko, Sarwoko; Revino, Revino (Universitas Pamulang, 2023)
This thesis discusses the design of a tool for planting lowland rice seeds which aims to reduce the time for planting rice seeds and reduce the impact of back pain. This research is a qualitative research with a descriptive design. Sampling with purposive sampling involved 100 rice farmers from one sub-district consisting of 10 villages in Lakbok sub-district to be interviewed and filled out a questionnaire to determine the wishes and needs of farmers for rice planting tools.The results of the analysis with the House of Quality (HOQ) in the QFD method of 23 questionnaire items resulted in 12 points that must be applied to the design, namely: the corner is not tapered, has three seed places, there are two iron pipe handles and hollow galvanized, coated with anti chat. carat, adjustable height, can plant 3 seeds at once, lightweight material, 95 cm wide, adjustable spacing, uncomplicated design, materials available in building shops.The results of anthropometric calculations on rice farmers obtained the size of the rice grower tool with a lever height (height) of 95.55 cm, the distance between the legs and the tool (base) 35.48 cm and the lever slope of 101.93 cm.The results of the test tools, the speed test of planting time with a land area of 1000 m2 resulted in 112 minutes 9 seconds or 1 hour 52 minutes 9 seconds. Capacity test, this tool has three lines, so this tool can represent two workers, so there is an increase in productivity of 66.67% with a tolerance of 10%, then the productivity of 56.67%. In total there is a 125.53% increase in productivity. In addition, this tool can reduce the burden on the waist because the designed tool is carried out standing upright when compared to planting rice in the conventional way.